Diverse Roles of Cellular Senescence in Skeletal Muscle Inflammation, Regeneration, and Therapeutics - Saito, Yuki; Chikenji, Takako S. (Frontiers in Pharmacology, 2021)
Skeletal muscle undergoes vigorous tissue remodeling after injury. However, aging, chronic inflammatory diseases, sarcopenia, and neuromuscular disorders cause muscle loss and degeneration, resulting in muscular dysfunction. Cellular senescence, a state of irreversible cell cycle arrest, acts during normal embryonic development and remodeling after tissue damage; when these processes are complete, the senescent cells are eliminated. However, the accumulation of senescent cells is a hallmark of aging tissues or pathological contexts and may lead to progressive tissue degeneration. The mechanisms responsible for the effects of senescent cells have not been fully elucidated. Here, we review current knowledge about the beneficial and detrimental effects of senescent cells in tissue repair, regeneration, aging, and age-related disease, especially in skeletal muscle. We also discuss how senescence of muscle stem cells and muscle-resident fibro-adipogenic progenitors affects muscle pathologies or regeneration, and consider the possibility that immunosenescence leads to muscle pathogenesis. Finally, we explore senotherapy, the therapeutic targeting of senescence to treat age-related disease, from the standpoint of improving muscle regeneration.